Assess the Maturity of Organization’s Project Management - M. N. Rudenko; Yu. D. Subbotina (Управленческое консультирование, 2019)
The article considers the models of evaluation of organizational maturity of project management, analyzes their advantages and disadvantages. The model of G. Kerzner’s maturity is analyzed in detail, the essence of each stage of the analysis of the organization is considered. In addition, the classification of types of personnel resistance to innovations related to project management is presented. Solutions to problems at different levels of maturity are proposed. Attention is focused on the factors that ensure the success of project management.